2023
DOI: 10.1111/tra.12885
|View full text |Cite
|
Sign up to set email alerts
|

Out of the ESCPE room: Emerging roles of endosomal SNX‐BARs in receptor transport and host–pathogen interaction

Abstract: Several functions of the human cell, such as sensing nutrients, cell movement and interaction with the surrounding environment, depend on a myriad of transmembrane proteins and their associated proteins and lipids (collectively termed “cargoes”). To successfully perform their tasks, cargo must be sorted and delivered to the right place, at the right time, and in the right amount. To achieve this, eukaryotic cells have evolved a highly organized sorting platform, the endosomal network. Here, a variety of specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 173 publications
0
11
0
Order By: Relevance
“…In HOPS KO cells, however, these tubules were generally depleted from CI-MPR ( Figure 5D ), suggesting a block in the entry of CI-MPR into ESCPE tubules rather than a general block in recycling ( Evans et al. , 2020 ; Simonetti et al. , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In HOPS KO cells, however, these tubules were generally depleted from CI-MPR ( Figure 5D ), suggesting a block in the entry of CI-MPR into ESCPE tubules rather than a general block in recycling ( Evans et al. , 2020 ; Simonetti et al. , 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many of our examined synaptic parameters remained unaltered or showed considerable variability, including our hypothesis that depletion of a synaptic endosomal sorting protein would disrupt synaptic recycling. This suggests the presence of redundant pathways compensating for SNX4 depletion, potentially involving other SNX-BAR complexes or endosomal sorting complexes like ESCPE, retriever, or retromer (Simonetti et al, 2023). Particularly SNX-BAR proteins, such as SNX7 and SNX30, are of potential interest for future research due to their ability to form selective complexes with SNX4 (Antón et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…SNX4 belongs to a subgroup of SNXs containing a C-terminal a Bin–Amphiphysin– Rvs (BAR) domain that recognizes and remodels curved endosome membranes (Cullen & Steinberg, 2018; Teasdale et al, 2001; Van Weering et al, 2012). While several SNX-BARs are associated with the retromer-related Endosomal SNX-BAR Sorting Complex for Promoting Exit (ESCPE)-1 (Simonetti et al, 2023), SNX4 forms a distinct sorting complex with SNX7, SNX30 (Antón et al, 2020; van Weering et al, 2012), SNX5 (Zhou et al, 2022), or SNX32 (Sugatha et al, 2023) for endosome-to-cell surface recycling pathways and autophagosome traffic (Traer et al, 2007; Van Weering et al, 2012; Zhou et al, 2022). SNX4 emerges as a central hub in this endosome recycling pathway as the expression of SNX4 is required for the stable SNX7 and SNX30 protein levels in cells (Antón et al, 2020).…”
mentioning
confidence: 99%
“…To delineate the subcellular localization of the ARL14 and ESCPE-1 complex, FlpIn HeLa cells expressing wild-type or the potentially active mutant (Q68L) of ARL14-mScalet were fixed and subjected to staining for SNX1 or SNX6. Given the pivotal role of SNX-BAR proteins in both endosome-to-plasma membrane recycling and endosome-to-TGN retrieval (Simonetti et al, 2023), we predicted that ARL14 and SNX would exhibit colocalization at least in one of these sites. These experiments revealed that both the wild-type and the Q68L variant ARL14-mScarlet were partially soluble in the cytoplasm, with some enrichment in punctate structures reminiscent of endosomes as well as at the plasma membrane (Fig.…”
Section: Arl14 Is Involved In Escpe-1 Mediated Traffickingmentioning
confidence: 99%